2019
DOI: 10.1016/j.jmmm.2018.11.127
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and heating efficacy of magnesium doped magnetite nanoparticles obtained by co-precipitation method

Abstract: Ferrofluids based on magnesium substituted magnetite nanoparticles Mg x Fe 3−x O 4 (x = 0.1; 0.2; 0.4) were synthesised by a chemical co-precipitation method. Their physical properties have been compared with those of the magnetite based ferrofluid obtained by the same synthesis route. Both XRD and TEM studies showed particle size decrease with the increased Mg content while DLS experiments pointed to the more prominent aggregation of Mg-containing nanoparticles. Magnetic properties investigation conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 49 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…A possible explanation can be associated with a greater number of large grains in the uncoated samples [27], which also increases the magnetic saturation and coercivity in the hysteresis loop of Figure 4a, and, conversely, the catechol coating avoids that clusterization due to negative electrostatic repulsions of hydroxyl groups formed around the Fe 3 O 4 [23]. Other possible physical explanations must be explored considering changes in the anisotropic energy of both presentations of MNPs (coated and uncoated) [15] and/or the possible existence of exchange interactions [28]. Indeed, several authors have observed the same magnetic modulating phenomenon with catechol-derived coatings [15,17,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation can be associated with a greater number of large grains in the uncoated samples [27], which also increases the magnetic saturation and coercivity in the hysteresis loop of Figure 4a, and, conversely, the catechol coating avoids that clusterization due to negative electrostatic repulsions of hydroxyl groups formed around the Fe 3 O 4 [23]. Other possible physical explanations must be explored considering changes in the anisotropic energy of both presentations of MNPs (coated and uncoated) [15] and/or the possible existence of exchange interactions [28]. Indeed, several authors have observed the same magnetic modulating phenomenon with catechol-derived coatings [15,17,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…However, the morpho-structural features and the magnetic properties of such materials are strongly dependent on the synthesis method used. Accordingly, several synthesis methods have been reported in the literature such as sol-gel [11], thermal decomposition [12,13], microemulsion [14], and co-precipitation [15][16][17][18]. Among them, co-precipitation is one of the most used methods due to the favorable synthetic conditions (i.e., high reaction yield, safe and inexpensive precursors and solvent).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ILP values of 3.8 and 1.75 nH m 2 kg –1 have been reported for Fe 3 O 4 NPs . Kusigerski et al achieved an ILP value of 0.57 nH m 2 kg –1 for Mg 0.1 Fe 2.9 O 4 NPs, which is slightly higher than that of the Mg 0.13 Fe 2.87 O 4 nanoferrites prepared by our group . Kallumadil et al investigated the heating potentials of commercially available iron oxide ferrofluids supplied by different companies with different iron contents, nanocrystallinity, and hydrodynamic diameter ( d h ).…”
Section: Resultsmentioning
confidence: 93%
“… 74 Kusigerski et al 77 achieved an ILP value of 0.57 nH m 2 kg –1 for Mg 0.1 Fe 2.9 O 4 NPs, which is slightly higher than that of the Mg 0.13 Fe 2.87 O 4 nanoferrites prepared by our group. 7500 Kallumadil et al investigated the heating potentials of commercially available iron oxide ferrofluids supplied by different companies with different iron contents, nanocrystallinity, and hydrodynamic diameter ( d h ). Calorimetric measurements recorded at 900 kHz with a field amplitude of 5.66 kA/m revealed ILP values ranging from 0.15 to 3.1 nH m 2 kg –1 (Resovist, ILP ≈ 3.1, d h : 60 nm, carboxy dextran–Fe 3 O 4 ).…”
Section: Resultsmentioning
confidence: 99%